홈트레이닝(home training) 참여자들의 자기결정성이 운동만족과 재이용에 미치는 영향 (경찰관련학과 재학생 대상) - 김상화(Sang-Hwa Kim) (한국컴퓨터정보학회논문지, 2022)
본 논문에서는 홈트레이닝에 참여하여 체력을 단련하고 있는 경찰관련학과 학생들의 자기결정성과 홈트레이닝 만족도와 재이용과의 관계를 알아보고자 하였다. 이를 위해 부산, 경남지역 D, S, K대학교 경찰행정학과, 경찰무도학과 재학생중 홈트레이닝에 참여한 경험이 있는 학생 349명을 대상으로 조사하였다. SPSSWIN VER 25+, AMOS 20.0 프로그램을 이용하여 자기결정성, 운동만족, 재이용 요인간의 관계를 검증한 결과, 첫째, 홈트레이닝 참여자의 자기결정성 하위요인인자율성, 유능감, 관계성은 홈트레이닝 만족도에 긍정적인 영향을 미쳤다. 둘째, 홈트레이닝 참여자의 운동만족은 홈트레이닝 재이용에 긍정적인 영향을 미쳤다. In this paper, we propose the relationship between self-determination, home training satisfaction, and reuse of police-related students who participate in home training and train their physical strength. The subjects of this study were students enrolled in the Department of Police Administration and Police Martial Arts at D, S, and K universities in Busan and Gyeongnam area. Among them, 349 students who had participated in home training were surveyed. As a result of verifying the relationship between self-determination, exercise satisfaction, and reuse factors using the collected data, SPSSWIN VER 25+, AMOS 20.0 program, First, autonomy, competence, and relationship, which are sub-factors of self-determination of home training participants, had a positive effect on home training satisfaction. Second, exercise satisfaction of home training participants had a positive effect on home training reuse. Based on the research results,It is essential to identify and manage what home training participants demand. It is believed that this can be a positive process for the development of home training. KCI Citation Count: 0